Workshop on Assisting in the Preparation of Classroom Action Research (PTK) for High School Physics Teachers in Aceh Tamiang - Nurulwati, Nurulwati; Susanna, Susanna; Saputri, Mawarni; Musdar, Musdar (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The Classroom Action Research (PTK) aims to enhance classroom learning quality for high school physics teachers in Aceh Tamiang, offering potential career advancements. Method: The PTK Assistance Workshop, a community service program, addressed the challenge of PTK development by directly engaging teachers via the Physics Subject Teachers Association (MGMP) Community. It focused on equipping teachers with skills for planning, executing, and documenting PTK reports. Practical Applications: Workshop outcomes included improved teacher proficiency in PTK implementation and potential journal article publications. Empowering teachers in PTK enhances classroom practices and supports educators' career progression. Conclusion: The workshop successfully bridged knowledge gaps among high school physics teachers, equipping them with essential skills for effective PTK implementation. This initiative not only benefits individual teachers but also promises to enhance overall classroom learning quality in the region.